Impact of Communication Technology on Student Behavior During Lectures - Kriyantono, Rachmat; Safitri, Reza; Fiaji, Noveria Anggraeni; Wijanarko, Wisnu; Krisdinanto, Nanang; Chandra Sari, Rohmah Nia; Nainggolan, Monica Trivena; Daros Airlangga, Muhammad Hafidz; Putri, Atma Amanda (Jurnal ILMU KOMUNIKASI, 2024)
Technological advancements have impacted education, influencing student behavior across different eras—1990s, 2000s, and today. This survey-based research uses conventional sampling techniques and supports the theory of technological determinism, showing how communication technology affects behavior, thought patterns, and social interactions. Face-to-face communication has largely been replaced by online interactions. The study finds that chatting remains a common activity while waiting for lecturers, and highlights a decline in reading habits. Instead, frequent use of mobile phone has become prevalent. The research underscores how technology reshapes both learning environments and student habits.